Study on Characteristics of the Vibration and Noise of High-Power Scroll Compressor - Chuang Wang; Zhen Wang; Weiguo Yan; Hongkun Li; Chunli Yang (Shock and Vibration)
With the rapid development of a high-power scroll compressor (HSC), the dynamic performance of a scroll compressor has an important impact on the vibration and noise of the whole compressor. So, the dynamic characteristics and structural acoustic radiation characteristics of HSC under dynamic excitation are studied by simulation and experiment in this paper. Firstly, the dynamic simulation model of HSC is established to analyze the time-domain and frequency-domain characteristics of bearing excitation and upper support excitation. At the same time, the finite element models of housing, upper support, and lower support are constructed to analyze the transient dynamic response of housing under the excitation source. Based on the vibration displacement of the housing surface, the prediction model of the housing radiated noise is also established, and then the radiated noise of the housing surface and the noise spectrum of the standardized test points are analyzed. Finally, the accuracy of the prediction model is verified by acoustic experiments. The experimental results show that the vibration and radiation noise of the housing can be accurately predicted by reasonable modeling to calculate the gas force and approximate the actual gas load. The vibration of the housing coupling system is the main source of the vibration characteristics of the HSC. The conclusions of the study can provide a reference for the low noise design of the HSC.